A Fluorophore-labeled Peptide of Human Ribosomal Protein S3 for the Detection of the 8-Oxoguanine within the Cells - Han, Se Hee; Hahm, Soo-Hyun; Tran, An Hue Vy; Park, Jin Woo; Chung, Ji Hyung; Park, Geon Tae; Han, Ye Sun (Bulletin of the Korean Chemical Society, 2015)
Detection and quantification of 8‐oxo‐7,8‐dihydroguanine (8‐oxoG) within cells are important for the study of the molecular mechanisms in cancer. Human ribosomal protein S3 (hRpS3), which involved in DNA repair, has high binding affinity to 8‐oxoG. We developed an imaging probe to detect 8‐oxoG using a specific peptide of hRpS3. Sequence analysis was conducted to elucidate the 8‐oxoG‐specific binding region of hRpS3, and three truncated mutants, D1 (amino acids 1–85), D2 (amino acids 86–159), and D3 (amino acids 160–242), were constructed. Both wild‐type‐hRpS3 and D2 were able to bind 8‐oxoG, which is consistent with the results of a previous report on the role of K134 in Drosophila melanogaster RpS3. We synthesized a specific peptide and covalently linked with a fluorophore (FPR‐552, similar to Cy3) to generate an 8‐oxoG imaging probe. Our 8‐oxoG S3‐probe successfully detected the presence of 8‐oxoG in damaged cells. Furthermore, this probe has threefold higher sensitivity than 8‐oxoG DNA lesion antibody.